Infantasies: An EPAT collective project. Issue 14 (6th December 2021) - Gibbons, Andrew; Peters, Michael A.; Delaune, Andrea; Jandrić, Petar; Sojot, Amy N.; Kupferman, David W.; Tesar, Marek; Johansson, Viktor; Cabral, Marta; Devine, Nesta; Hood, Nina
Abstract: This is a collective writing project that is part of the larger design of Infantologies, Infanticides and Infantilizations; a quartet that explores the philosophy of infants from thematic perspectives, that puts infants at the centre of our reflections, and that encourages a different academic style of thinking.